A review on enhancing employability skills in technical and vocational education and training through service-learning - Mohd Zaid, Mohd Fakhrul Azizie; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
In the fast-changing and borderless world, the evolving of Industrial Revolution indirectly has brought its impact to the youth unemployment and development. Align with these changes and facts, employability skills within graduates are among the skills that demand more attention by educational institution to meet the industry needs. Over the years, these skills have fast become compulsory rather than being desired among the employers in choosing better graduates. However, literatures have indicated that service-learning has been widely tested in providing students to connect and deal with real life experiences within the community, which can empower their cognitive and employability skills. This paper serves as an early stage of study on the concept of employability skills, concept of service-learning and the needs to enhance employability skills in TVET through service-learning to secure their job. In summary, this paper concludes and recommends that in order to decrease the mismatch of skills among students, teachers including TVET instructors need to empower their instructional pedagogy using service-learning as a training device that can bring more benefits within the learning environments.